Examples

Example 1

Example 2

Example 3

Example 4 Important

Example 5

Example 6

Example 7

Example 8 Important

Example 9 Important

Example 10

Example 11 Important

Example 12

Example 13 Important

Example 14

Example 15

Example 16 Important

Example 17

Example 18 Important

Example 19

Example 20 Important

Example 21 Important

Example 22

Example 23 Important

Example 24

Example 25 Important

Example 26 Important

Example 27

Example 28 Important

Example 29 Important

Example 30 Important

Example 31 Important

Example 32 Important

Example 33 Important

Example 34 Important

Example 35

Example 36 Important

Example 37

Question 1 Deleted for CBSE Board 2024 Exams

Question 2 Deleted for CBSE Board 2024 Exams

Question 3 Deleted for CBSE Board 2024 Exams

Question 4 Important Deleted for CBSE Board 2024 Exams

Question 5 Deleted for CBSE Board 2024 Exams You are here

Question 6 Deleted for CBSE Board 2024 Exams

Question 7 Deleted for CBSE Board 2024 Exams

Question 8 Deleted for CBSE Board 2024 Exams

Question 9 Deleted for CBSE Board 2024 Exams

Question 10 Deleted for CBSE Board 2024 Exams

Question 11 Deleted for CBSE Board 2024 Exams

Question 12 Deleted for CBSE Board 2024 Exams

Question 13 Important Deleted for CBSE Board 2024 Exams

Question 14 Important Deleted for CBSE Board 2024 Exams

Last updated at April 16, 2024 by Teachoo

Question 5 Find the equation of the tangent to the curve y = (𝑥 − 7)/((𝑥 − 2)(𝑥 − 3)) at the point where it cuts the x-axis.Slope of the tangent to the curve is 𝑑𝑦/𝑑𝑥 = ((𝑥 − 7)^′ [(𝑥 − 2) (𝑥 − 3)]− (𝑥 − 7) [(𝑥 − 3) (𝑥 − 2)]^′)/((𝑥 − 2)^2 (𝑥 − 3)^2 ) 𝑑𝑦/𝑑𝑥 = (1 × (𝑥 − 2) (𝑥 − 3) − (𝑥 − 7)[(𝑥 − 3)^′ (𝑥 − 2) + (𝑥 − 3) (𝑥 − 2)^′ ])/((𝑥 − 2)^2 (𝑥 − 3)^2 ) 𝑑𝑦/𝑑𝑥 = ((1) (𝑥 − 2) (𝑥 − 3) − (𝑥 − 7)[1 × (𝑥 − 2) + (𝑥 − 3) × 1])/((𝑥 − 2)^2 (𝑥 − 3)^2 ) 𝑑𝑦/𝑑𝑥 = ((𝑥 − 2) (𝑥 − 3) − (𝑥 − 7)(2𝑥 − 5))/((𝑥 − 2)^2 (𝑥 − 3)^2 ) 𝑑𝑦/𝑑𝑥 = ((𝑥 − 2) (𝑥 − 3) )/((𝑥 − 2)^2 (𝑥 − 3)^2 )−(𝑥 − 7)(2𝑥 − 5)/((𝑥 − 2)^2 (𝑥 − 3)^2 ) 𝑑𝑦/𝑑𝑥 = (1 )/((𝑥 − 2) (𝑥 − 3) )−((𝑥 − 7))/((𝑥 − 2) (𝑥 − 3) ) × ((2𝑥 − 5))/((𝑥 − 2) (𝑥 − 3) ) 𝑑𝑦/𝑑𝑥 = (1 )/((𝑥 − 2) (𝑥 − 3) )−𝑦 × ((2𝑥 − 5))/((𝑥 − 2) (𝑥 − 3) ) 𝒅𝒚/𝒅𝒙 = (𝟏 − 𝒚(𝟐𝒙 − 𝟓))/((𝒙 − 𝟐) (𝒙 − 𝟑) ) We need to find Equation of tangent at the point where the curve cuts the x axis, Thus, y = 0 We need to find value of x Putting y = 0 in equation of curve 0 = (𝑥 − 7)/(𝑥 − 2)(𝑥 − 3) ∴ x = 7 Thus, curve cuts the x-axis at point (7, 0) Finding Slope at point (7, 0) 𝑑𝑦/𝑑𝑥 = (1 − 𝑦(2𝑥 − 5))/((𝑥 − 2) (𝑥 − 3) ) Putting x = 7, y = 0 = (1 − 0[2(7)−5])/((7 − 2) (7 − 3) ) = 1/(5 × 4) = 𝟏/𝟐𝟎 Now, Equation of the tangent at point (7, 0) with slope 1/20 is 𝑦 −𝑦_1= 𝑚 (𝑥 − 𝑥1) 𝑦−0= 1/20 (𝑥−7) 20𝑦=𝑥−7 𝟐𝟎𝒚−𝒙+𝟕=𝟎